Perlindungan Praakad dalam Undang-Undang Kontrak Islam - Shofian Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2007)

(untitled)
The protection towards the contracting parties in the Islamic law of contract extends as early as at the formulation of contract. The objective of this protection is to avoid the contracting parties from making any unlawful contracts leading to be useless and baseless. This study aims at examining the protection at the pre-contract stage in the Islamic law of contract. Thus, this study focuses on the characteristics of the protection as discussed by the Muslim jurists. Furthermore, it compares the protection with the similar provision in the Malaysian Contract Act 1950. In general, the pre-contract protection in Islamic law of contract seems more comprehensive in protecting the contracting parties